The Impact of War on the Transformation of the Strategic Paradigm of Organizational Change Management in Conditions of Increased National Security Threats - Viunyk, Olha; Kurnosenko, Larysa; Lashchyk, Iryna; Tarasov, Serhii; Shtangret, Andriy (Journal of Ecohumanism, 2024)
In times of war or increased national security threats, the traditional paradigms of managing these transitions must adapt to the rapidly changing circumstances. War alters the economic, social, and political environments dramatically, necessitating that organizations quickly adapt to ensure survival and continue operations. This requires a reevaluation of strategic objectives and management practices to align with the broader context of national security. The purpose of the article is to characterize the features of the impact of war on the change of the strategic paradigm of organizational change management in conditions of increased national security threats. The object of the study is the system of organizational change management in conditions of increased national security threats. The methodology of the study involves the use of the IDEF0 method. As a result of the study, a modern IDEF0 model of transformation of the strategic paradigm of organizational change management in conditions of increased national security threats was presented.